Urogenitální poranění u pacientů u polytraumatu: pětiletá epidemiologická studie - Čapka, D; Klézl, P; Fric, M; Grill, R (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2021)
INTRODUCTION The authors present an overview of polytrauma patients with urinary tract injuries managed in the Level I trauma centre. The purpose of this study was to evaluate the frequency of injuries to the urinary system, the mechanism of their injury and the method of treatment in the cohort of polytrauma patients treated in the trauma centre. MATERIAL AND METHODS Between 2012 and 2016, a total of 231 polytrauma patients were treated, of whom 47 (20.3%) also suffered a urotrauma. The renal trauma, ureteral trauma, bladder trauma and urethral trauma were classified according to the American Association for the Surgery of Trauma (AAST) scoring scale. RESULTS The non-operative treatment was opted for in 24 patients (86%) with Grade I and II kidney injury, whereas a surgical revision was indicated in line with the European Association of Urology (EAU) Guidelines in 9 patients (100%) with Grade III renal trauma or higher. The bladder trauma was treated non-operatively in two patients (22.2%) with Grade I and II bladder injury and operatively in 7 patients (77.7%) with Grade III injury or higher. After the operative management of urogenital injuries in 18 patients (38%), complications occurred in 7 patients (39%). A total of 7 patients (14.9%) died as a consequence of polytrauma with urinary tract injuries and in 5 of them the death occurred within 30 days of polytrauma, but no urinary tract injury led directly to death of the patient. DISCUSSION Kidneys are the most frequently injured uropoietic organ. A civilian kidney trauma is present in up to 5% of trauma patients and accounts for 24% of abdominal injuries. The computed tomography scanning with intravenous contrast (CT IVU) remains the Gold Standard. In recent decades there was a shift in treating the prevailing majority of patients with a kidney trauma, namely from surgical revision to non-operative treatment. This trend was also observed by the authors in their own cohort. CONCLUSIONS Based on the evaluation of their own cohort of patients, the authors state that the diagnostic algorithm including CT IVU and also UCG in indicated patients are adequate to timely diagnose the urinary tract injuries, including polytraumas. The study confirmed that the most frequent injury to the urinary tract in polytrauma patients is the kidney trauma and that the urinary tract injury is not usually the cause of death in polytraumatized patients. Key words: polytrauma, urotrauma, urogenital organ injury, kidney, urinary bladder, AAST.
Keywords: polytrauma; poranění břicha; Injury Severity Score; Kidney; Multiple Trauma; Thoracic Injuries; lidé; retrospektivní studie; skóre závažnosti úrazu; Trauma Centers; ledviny; Retrospective Studies; traumatologická centra; poranění hrudníku; Abdominal Injuries; Humans